Effect of Orange Peel Waste Adsorbent Mass on Lead (Pb) Metal Biosorption in Artificial Liquid Waste: Pengaruh Massa Adsorben Limbah Kulit Jeruk terhadap Biosorpsi Logam Timbal (Pb) dalam Limbah Cair Buatan - Djamilah Arifiyana; Ratih Kusuma Wardani (Akademi Farmasi Surabaya, 2023)
In this study, orange peel was used as an adsorbent to determine the adsorption properties of lead metal. The orange peel used in this study came from waste generated by a fruit juice shop. The mass variation of the adsorbent was studied to determine its effect on the adsorption of lead metal. Mass variations used include 0.25-1.5 gram. The operating conditions used in this study included the preparation of 50 mL of 50 mg/L Lead solution, the pH of the mixture was adjusted to pH 4, the stirring speed was 100 rpm for 180 minutes and at 25℃. The results showed that the highest % adsorption was achieved at an adsorbent mass of 0.75 grams, which was 92.9% (2.5 mg/g), while the highest adsorption capacity was obtained at the use of an adsorbent mass of 0.25 grams (7.27 mg/g). Both the decrease in % adsorption and adsorption capacity that occurred in the use of the mass variation of the adsorbent were mostly caused by the aggregation process.